Deciphering Mpox: Understanding Pathophysiology, Perception, and Strategies for the Concerned Approach - Naaz, Shazia; Jyothi, Lakshmi (New Visions in Medicine and Medical Science Vol. 2, 2024)
Recent advancements have furthered our understanding of Mpox pathogenesis, highlighting the virus's complex interactions with the human immune system. Studies now emphasize the critical role of mRNA vaccines in providing a potent immune response, underscoring the potential for broader protective measures against the virus. While the globe struggles to contain the Coronavirus disease- 19 (COVID-19) pandemic, the upsurge of isolated cases of other viral diseases like Monkey pox (Mpox) has raised alarm. On July 23, 2022, the world health organization (WHO) director-general, Tedros Adhanom Ghebreyesus, PhD, overruled the WHO Emergency Committee (EC), which had voted 6-9 against declaring a public health emergency of international concern (PHEIC), and declared the current Mpox outbreak a PHEIC. In the lack of easily accessible prophylaxis or treatment, prompt case identification is critical for containment. The fact that some of the nine cases of mpox reported in India have no travel history, indicating that the disease may spread through droplet infection, nucleus, or aerosol transmission, is concerning the general public. The latest outbreak in Europe and North America is most likely sustained by human-to-human transmission, unlike the cases discovered in Africa, according to the letter’s authors. The virus can transfer from one person to another through direct contact with lesions, bodily fluids, respiratory droplets, or fomites. However, the infection is typically a zoonosis in the African continent. Besides, the reluctance of people to even disclose when they have symptoms owing to social stigma, adds to the challenge. To combat the common misconceptions, the researchers demanded an ‘urgent’ revision to the term ‘Mpox.’ In contrast to smallpox, Mpox disease remains endemic in some parts of the world (primarily West and Central Africa). The outlook is better for the West African clade, which has a case fatality rate (CFR) of less than 1%. Whereas, the Central Basin clade (also called the Central African clade) is more deadly, with a CFR of up to 11% in young unvaccinated individuals. New research highlights advanced understanding of Mpox pathogenesis, including detailed virus localization in tissues, especially in immunocompromised patients. Studies show severe or fatal outcomes are more common in these groups, emphasizing the need for targeted surveillance and management strategies.